MURIEL SPARK’S CONTRIBUTION TO THE DEVELOPMENT OF ENGLISH NOVEL - Ganieva Orzigul Khayriddinovna; Sodikova Visola Yunusovna (Journal Park Publishing, 2024)
Muriel Spark is considered to be one of the prominent writers of English Literature and her contribution to the development of English Novel is enormous. Her novels “The Prime of Miss Jean Brodie”, “Memento Mori”, “The Girls of Slender Means”, “The Driver’s Seat”, “A Far Cry from Kensington” and “Loitering with Intent” explore themes such as identity, religion, power dynamics and the human condition, demonstrating her ability to grasp these complexities of man’s nature at a depth and accuracy. The following paper strives to explore the author’s contribution to the development of English Literature as a novelist. Muriel Spark skill to infuse wit, depth, and timeless relevance into her works has cemented her position as an important figure in the literary canon.
Keywords: Muriel Spark, author, character, literary work, internal, external, writer, literature, themes, influence, novel.